ASSESSMENT OF FACTORS INFLUENCING THE USE INTENSITY OF IMPROVED SOIL MANAGEMENT PRACTICES IN IMO STATE, NIGERIA - Emeka Emmanuel OSUJI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study evaluated the factors influencing the use intensity of improved soil management practices in Imo State, Nigeria. Data were obtained from 209 farmers with the aid of structured questionnaire. Data were analyzed using descriptive statistical tools such as the mean, frequency and percentages. The findings revealed that age, education, farming experience, household size, occupation and farm size etc are important factors influencing the use intensity of improved agricultural practices in the area. These factors probably could either mar or enhance the use intensity of improved agricultural practices. The study revealed that extension contacts are very vital in exposing the farmers to new innovations and modern farming technologies which improves the farm productivity and income of the farmers. Therefore, there is the need for increased extension services and technological education of the rural farmers via both the government and private enterprises to enhance farmers’ perception and dispositions to socio-economic factors.